Hair Growth Activity Test of Hair Tonic that Contain Combination of Green Tea Leaf Extract and Celery Leaf Extract - Nursiyah Nursiyah; Romadhiyana Kisno Saputri; Akhmad Al-Bari (Universitas Islam Negeri Alauddin Makassar, 2021)
Hair loss is an abnormality where the amount of hair is less or more than normal with or without visible thinning. Excessive hair loss can lead to baldness. The prevalence of hair loss in women aged 14-28 years in Jakarta is 50%, and in Surabaya, it occurs in 53.3% of hijab users. One of the formulations that could be used to prevent hair loss is hair tonic formulations. Hair tonic is a cosmetic formulation that functions to stimulate hair growths, both in normal hair and in hair loss and baldness. Hair tonic can be developed from natural ingredients such as green tea leaves, celery leaves, or a combination of both. Green tea leaves contain epigallocatechin-3-gallate and flavonoids which have hair growth activity, while celery leaf (Apium graveolens L.) contain apigenin compounds that have hair growth activity. This research aims to formulation and evaluation of hair tonic contain ethanol extract of green tea leaves (Camellia Sinensis L.), celery leaf (Apium grave lens L.), and a combination of ethanol extract of green tea leaves (Camellia Sinensis L.) and celery leaf (Apium grave lens L.) in guinea pigs. This study is an experimental type of quantitative research with a true experimental design. laboratory and Completely Randomized Design (CRD). Hair tonic formulations were made with 6 formulations given to 6 groups of guinea pigs with a total of 4 guinea pigs in each group. The formulations used were negative control, positive control of celery leaf extract, positive control of green tea leaf extract, formulation of 1 green tea leaf 7,5% and celery leaf extract 2,5%, formulation of 2 green tea leaf 5% and celery leaf extract 5%, formulation 3 green tea leaf extract 2,5% and celery leaf extract 7,5%. Evaluation of hair tonic formulations was carried out by physical evaluation with organoleptic tests and pH tests. Evaluation of hair growths activity observed the hair growth of guinea pigs every 7 days for 28 days and measured it with a caliper. The results of the organoleptic test of organoleptically stable hair tonic formulations were assessed from the color, smell, and texture that did not change. The results of the pH test met the requirements for the skin's pH value of 4.5-6.5. The results of the hair growth test on hair tonic formulations showed that all formulations could grow hair in guinea pigs. Green tea leaves (Camellia sinensis L) extract, celery leaves (Apium grave lens L), and the combination of green tea leaves (Camellia sinensis L) extract and celery leaves (Apium grave lens L) extract can be formulated and used as hair growth in guinea pigs. The best grow hair fast formulation is a combination of green tea leaves extract: celery leaves extract is 2,5%:7,5%.